2019
DOI: 10.1177/0308022619830906
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between home environment and energy expenditure of community-dwelling older adults

Abstract: Introduction: High energy expenditure by healthy older individuals has numerous benefits, and housework and exercises done at home are among the most common physical activities. However, there is little knowledge about how characteristics of the urban built environment could impact energy expenditure for moderate and vigorous daily activities. This study characterizes accessibility and a number of physical barriers, investigates the relationship between home environmental press and energy expenditure at home, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We included studies with different designs (e.g., observational, pre-post) and publication dates ranged from 1995 to 2020. Studies were from the following locations: Canada (6) (Haney, Fletcher, & Robertson-Wilson, 2018; Harrison et al, 2010; Patry et al, 2019; Regan et al, 2016; Reid, 2004; Voss, Pope, & Copeland, 2020); Sweden (4) (Lilja & Borell, 1997; Niva & Skär, 2006; Petersson, Lilja, & Borell, 2012; Thordardottir, Fange, Chiatti, & Ekstam, 2020); United States (4) (Cress, Orini, & Kinsler, 2011; Joseph & Zimring, 2007; Joseph, Zimring, Harris-Kojetin, & Kiefer, 2005; Kotlarczyk et al, 2020); Australia (3) (Aplin, de Jonge, & Gustafsson, 2015; Nathan, Wood, & Giles-Corti, 2014b; Pettigrew et al, 2020); Finland (1) (Portegijs, Rantakokko, Viljanen, Rantanen, & Iwarsson, 2017); Germany (1) (Benzinger et al, 2014); Korea (1) (Park, Park, Hancox, Castaneda-Gameros, & Koo, 2019); The Netherlands (1) (van den Hombergh, Schouten, van Staveren, van Amelsvoort, & Kok, 1995); Spain (1) (Perez-Hernandez et al, 2018); and Taiwan (1) (Cheng, Wang, Tang, Chu, & Chen, 2014). The included studies were from higher income countries (The World Bank Group, n.d.).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We included studies with different designs (e.g., observational, pre-post) and publication dates ranged from 1995 to 2020. Studies were from the following locations: Canada (6) (Haney, Fletcher, & Robertson-Wilson, 2018; Harrison et al, 2010; Patry et al, 2019; Regan et al, 2016; Reid, 2004; Voss, Pope, & Copeland, 2020); Sweden (4) (Lilja & Borell, 1997; Niva & Skär, 2006; Petersson, Lilja, & Borell, 2012; Thordardottir, Fange, Chiatti, & Ekstam, 2020); United States (4) (Cress, Orini, & Kinsler, 2011; Joseph & Zimring, 2007; Joseph, Zimring, Harris-Kojetin, & Kiefer, 2005; Kotlarczyk et al, 2020); Australia (3) (Aplin, de Jonge, & Gustafsson, 2015; Nathan, Wood, & Giles-Corti, 2014b; Pettigrew et al, 2020); Finland (1) (Portegijs, Rantakokko, Viljanen, Rantanen, & Iwarsson, 2017); Germany (1) (Benzinger et al, 2014); Korea (1) (Park, Park, Hancox, Castaneda-Gameros, & Koo, 2019); The Netherlands (1) (van den Hombergh, Schouten, van Staveren, van Amelsvoort, & Kok, 1995); Spain (1) (Perez-Hernandez et al, 2018); and Taiwan (1) (Cheng, Wang, Tang, Chu, & Chen, 2014). The included studies were from higher income countries (The World Bank Group, n.d.).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies observed participants in private dwellings (Aplin et al, 2015; Benzinger et al, 2014; Niva & Skär, 2006; Patry et al, 2019; Perez-Hernandez et al, 2018; Petersson et al, 2012; Portegijs et al, 2017; Reid, 2004; Thordardottir et al, 2020; van den Hombergh et al, 1995); six observed participants in collective dwellings (Cheng et al, 2014; Joseph et al, 2005; Joseph & Zimring, 2007; Kotlarczyk et al, 2020; Nathan et al, 2014a, 2014b; Voss et al, 2020); five studies compared between dwellings (Cress et al, 2011; Harrison et al, 2010; Lilja & Borell, 1997; Park et al, 2019; Pettigrew et al, 2020), while two studies observed older adults as they transitioned to a collective dwelling (Haney et al, 2018; Regan et al, 2016). The age range of participants in private dwellings was from 25 to 65 years, and for people in collective dwellings it was from 65 to 97 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hazards we face in activities also depend on the environment and participation in activities depends on how successfully we meet the challenges that the environment presents to individuals. 7 …”
Section: Introductionmentioning
confidence: 99%